LIBERAL FEMINISM REFLECTED IN KATY PERRY’S PART OF ME MUSIC VIDEO: A Multimodal Critical Discourse Analysis. - Fallah Salsabila; Ichwan Suyudi (Universitas Lambung Mangkurat, 2023)
This research aims to find and elaborate the visual grammar found in Katy Perry’s Part of Me Music Video and which scenes from the video contain Liberal Feminism values. This research employed descriptive qualitative method. The data of this research are visual images from a music video. The data were obtained from several scenes of Katy Perry’s Music Video titled Part of Me that were being captured by the researcher. The researcher used theory of visual grammar by Kress and Leeuwen and Fairclough’s theory regarding critical discourse analysis. The result of this research showed that there were 5 scenes that have liberal feminism values from a 4 minutes long music video.